تطبيقات النمذجة الرياضية لمؤشرات التشبع الغذائي في بحيرة سد الثورة - رندى قواف (Tishreen University, 2019)
تم في هذا البحث دراسة نظريةلأهم النماذج الرياضية العالمية لمؤشرات التشبع الغذائي في البحيرات، والتي تتعلق بالفوسفور الكليوالنتروجين الكلي والكلوروفيلa والشفافية أوعمق Secchi disk ، وتطبيق هذه النماذج على بحيرة سد الثورة، وذلك من خلال دراسة حقلية لتلك المؤشرات (TP,TN,Chla,CD) بأخذ عينات من مواقع مختلفة منها، واجراء تحاليل شهرية ودورية لها استمرت من شهر تشرين الأول 2009 إلى شهر أيلول 2010 إذ تمت المقارنة بين خمس علاقات ارتباط للكلوروفيلa والفوسفور الكلي، تم اختيار النموذج الأفضل فيما بينها كما تمت دراسة علاقة ارتباط للكلوروفيلa وعمق secchi-disk وأخيراً تم التوصل إلى مجموعة استنتاجات وتوصيات يحتاج الأخذ بها وتطبيقها بشكل متكامل إلى إدارة سليمة لجودة المياه. In this research , a theoretical study was conducted for the most important international mathematical models for eutrophication's indicators in lakes, which include (total phosphorus concentration, total nitrogen concentration, total chlorophyll a concentration, Secchi-disk depth) and applying these models on Al-Thawra Dam lake through field study for the indicators (TP, TN, Chla, CD), and by taking samples from different locations and analyzing tests monthly and periodically in the period from October 2009 to September 2010, and by comparing between the correlations relations for chlorophyll a and total phosphorus, the best model was chosen using a computer program in visual basic language, another study was applied on chlorophyll -Secchi disk depth correlation.   Finally, several conclusions and recommendations were reached and in order to perfectly apply them, well management is needed for good water quality.